Human factors in general practice: early thoughts on the educational focus for specialty training and beyond - McKay, John; Pickup, Laura; Atkinson, Sarah; McNab, Duncan; Bowie, Paul (Taylor & Francis, 2016)
In the third article in the series, we describe the outputs from a series of roundtable discussions by Human Factors experts and General Practice (GP) Educational Supervisors tasked with examining the GP (family medicine) training and work environments through the lens of the systems and designed-centred discipline of Human Factors and Ergonomics (HFE). A prominent issue agreed upon proposes that the GP setting should be viewed as a complex sociotechnical system from a care service and specialty training perspective. Additionally, while the existing GP specialty training curriculum in the United Kingdom (UK) touches on some important HFE concepts, we argue that there are also significant educational gaps that could be addressed (e.g. physical workplace design, work organisation, the design of procedures, decision-making and human reliability) to increase knowledge and skills that are key to understanding workplace complexity and interactions, and supporting everyday efforts to improve the performance and wellbeing of people and organisations. Altogether we propose and illustrate how future HFE content could be enhanced, contexualised and integrated within existing training arrangements, which also serves as a tentative guide in this area for continuing professional development for the wider GP and primary care teams.